Repurposing chlorpromazine to treat COVID-19: The reCoVery study - Plaze, M. (Encephale, 2020)
OBJECTIVES: The ongoing COVID-19 pandemic has caused approximately 2,350,000 infections worldwide and killed more than 160,000 individuals. In Sainte-Anne Hospital (GHU PARIS Psychiatrie & Neuroscience, Paris, France) we have observed a lower incidence of symptomatic forms of COVID-19 among patients than among our clinical staff. This observation led us to hypothesize that psychotropic drugs could have a prophylactic action against SARS-CoV-2 and protect patients from the symptomatic and virulent forms of this infection, since several of these psychotropic drugs have documented antiviral properties. Chlorpromazine (CPZ), a phenothiazine derivative, is also known for its antiviral activity via the inhibition of clathrin-mediated endocytosis. Recentin vitro studies have reported that CPZ exhibits anti-MERS-CoV and anti-SARS-CoV-1 activity. METHODS: In this context, the ReCoVery study aims to repurpose CPZ, a molecule with an excellent tolerance profile and a very high biodistribution in the saliva, lungs and brain. We hypothesize that CPZ could reduce the unfavorable course of COVID-19 infection among patients requiring respiratory support without the need for ICU care, and that it could also reduce the contagiousness of SARS-CoV-2. For this purpose, we plan a pilot, multicenter, randomized, single blind, controlled, phase III therapeutic trial (standard treatment vs. CPZ + standard treatment). CONCLUSION: This repurposing of CPZ for its anti-SARS-CoV-2 activity could offer an alternative, rapid strategy to alleviate infection severity. This repurposing strategy also avoids numerous developmental and experimental steps, and could save precious time to rapidly establish an anti-COVID-19 therapy with well-known, limited and easily managed side effects.